2004
DOI: 10.1038/429522a
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Atlantic leatherback turtle movements

Abstract: The overall extent of habitat use by leatherback turtles in the North Atlantic, and hence their possible interactions with longline fisheries, is unknown. Here we use long-term satellite telemetry to reveal that leatherbacks range throughout the North Atlantic, indicating that closing limited areas to longline fisheries will probably have only partial success in reducing turtle bycatch. Although turtles dive very deeply on occasion (one descended to a maximum depth of 1,230 metres, which represents the deepest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 6 publications
8
151
0
3
Order By: Relevance
“…Leatherbacks undergo the longest migrations of any sea turtle species, crossing ocean basins to forage on cnidaria zooplankton such as jellyfish and salps (James and Herman, 2001;Hays et al, 2004;James et al, 2005;Benson et al, 2007a, b). Their large size and unique thermoregulatory adaptations allow them to inhabit tropical and temperate oceans (Frair et al, 1972;Greer et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Leatherbacks undergo the longest migrations of any sea turtle species, crossing ocean basins to forage on cnidaria zooplankton such as jellyfish and salps (James and Herman, 2001;Hays et al, 2004;James et al, 2005;Benson et al, 2007a, b). Their large size and unique thermoregulatory adaptations allow them to inhabit tropical and temperate oceans (Frair et al, 1972;Greer et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Leatherbacks thermoregulate in varied thermal environments (Paladino et al 1990), make epic migrations (Morreale et al 1996, Eckert & Sarti 1997, Ferraroli et al 2004, Hays et al 2004, James et al 2005, have the fastest growth rate (Zug & Parham 1996) and largest reproductive output (Reina et al 2002) of any turtle, and are among the largest living reptile species (200 to 900 kg). Further, leatherbacks are specialist predators for gelatinous zooplankton prey (Bjorndal 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The recent dramatic decline in global leatherback populations is chiefly due to extensive egg-harvesting and adult mortality due to direct hunting and incidental fisheries interactions within the leatherbacks' extensive range (see analyses by Spotila et al 2000, Ferraroli et al 2004, Hays et al 2004, Lewison et al 2004, Troëng et al 2004, James et al 2005, Kaplan 2005). However, effects of climatically altered resource availability on energy acquisition, which have not been considered in these analyses, may also have significant impacts on the viability of leatherback populations.…”
Section: Introductionmentioning
confidence: 99%
“…Both (2) and (3) would minimize potential injuries to turtles and researchers. Hays et al (2004b) reported successful deployments of similar recorders by attaching an ADR directly to a flipper tag with a wire, which can be cut to retrieve the ADR without removing the flipper tag. More research is necessary to reduce handling time and mutilation of animals when electronic recorders and transmitters are deployed to study their natural behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely deep (>1000 m) and long dives reported in Eckert et al (1989) were not found in our study. Although it has been reported that leatherback turtles can dive deeper than 1000 m and longer than 30 min, these dives are rare (Hays et al 2004b). The sample sizes of these studies were too small to make conclusive remarks on diving behavior of nesting leatherback turtles.…”
Section: Tracked a Loggerhead Turtlementioning
confidence: 99%